Privacy preserving in online social networks (Facebook system) - Lin, Peizhen (2014)
Online Social Networks (OSN) facilitate connections between people based on shared interests, values, and membership in groups. They make it easier for people to connect and communicate with others in their networks using the Web as the interface.